2015
DOI: 10.1016/j.ijsu.2015.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Current status of minimally invasive surgery for gastric cancer: A literature review to highlight studies limits

Abstract: A multicenter study with a large number of patients is now needed to further investigate the safety and efficacy as well as long-term outcomes of robotic surgery, traditional laparoscopy and the open approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Although patient selection has an important role in the feasibility of achieving an adequate oncologic resection and lymph node retrieval, a surgical approach was likewise found to be an important factor in the likelihood of resecting at least 15 nodes. Proponents of robotic technology, in particular, cite greater technical precision, more degrees of freedom in instrument articulation, and better visualization of anatomy relative to other surgical approaches [10]. With most of the experience and literature regarding surgery for gastric cancer coming from the East, previously published studies show a greater quantity of lymph nodes harvested during minimally invasive surgery, yet there is a general lack of consensus regarding improved R0 resection rates on the basis of the approach alone [11,[19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although patient selection has an important role in the feasibility of achieving an adequate oncologic resection and lymph node retrieval, a surgical approach was likewise found to be an important factor in the likelihood of resecting at least 15 nodes. Proponents of robotic technology, in particular, cite greater technical precision, more degrees of freedom in instrument articulation, and better visualization of anatomy relative to other surgical approaches [10]. With most of the experience and literature regarding surgery for gastric cancer coming from the East, previously published studies show a greater quantity of lymph nodes harvested during minimally invasive surgery, yet there is a general lack of consensus regarding improved R0 resection rates on the basis of the approach alone [11,[19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of minimally invasive surgical methods are proven and well published [6,[10][11][12][13][14][15][16]. With advantages such as decreased postoperative pain and shorter length of hospital stay, minimally invasive techniques are heralded as a significant development in the progress of general surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric surgery is one of the most relevant and developed fields of minimally invasive surgery[2]. Although general international support has emerged in its application at dedicated centers, practitioners must still assess which patients would benefit most from these technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers are currently debating several points, 32 first, the need to perform an adequate lymphadenectomy with minimally invasive techniques. With laparoscopy, surgeons can feasibly remove at least 15 lymph nodes, 26 but research has shown a statistically significant difference in favor of the open approach regarding the total number of retrieved lymph nodes.…”
Section: Discussionmentioning
confidence: 99%